Pathways to the Glass Cliff: A Risk Tax for Women and Minority Leaders?. (22nd November 2019) - Glass, Christy; Cook, Alison
Abstract: Do women and racial/ethnic minority leaders pay a risk tax on their way to the top? Theories of the glass cliff have focused on the penalties imposed upon women and minority leaders due to bias and discrimination at the time of appointment to top leadership positions. Much less attention has focused on the strategic agency these leaders exercise in response to bias across the career. This paper advances theory and research on the glass cliff by analyzing the choices, decisions, and priorities of white women and people of color that, across the career, result in their appointment to glass cliff positions. Our analysis relies on in-depth, semi-structured interviews with 33 senior leaders across a range of industries. Our findings suggest that rather than isolated instances of high-risk promotions, glass cliff appointments represent the culmination of a long-term career strategy centered on risk and risk-taking. We find evidence that these leaders pay a significant risk tax in order to achieve upward mobility in their organizations.